2017
DOI: 10.3390/met7020055
|View full text |Cite
|
Sign up to set email alerts
|

Urban Mining and Electrochemistry: Cyclic Voltammetry Study of Acidic Solutions from Electronic Wastes (Printed Circuit Boards) for Recovery of Cu, Zn, and Ni

Abstract: Abstract:We report potentiodynamic studies to characterize copper, nickel and zinc leaching solutions from electronic waste. The metals were leached using oxygen and sulfuric acid (pH = 1.5). As is known, reduction potentials are determined using thermodynamics laws, and metal recovery strategies from electronic waste are usually considered according these thermodynamic values. Pourbaix-type diagrams are not appropriate to plan strategies in electrochemical processing. Therefore, knowledge of electrode potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…According to the results found in this work, both WEEE and MW have interesting Au, Cu, and Ag values to be processed by dynamic leaching using the O 2 -thiosemicarbazide system. These values are consistent with those reported in different works [ 1 , 5 , 7 , 11 , 12 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the results found in this work, both WEEE and MW have interesting Au, Cu, and Ag values to be processed by dynamic leaching using the O 2 -thiosemicarbazide system. These values are consistent with those reported in different works [ 1 , 5 , 7 , 11 , 12 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The above, join with the increase of severe environmental protection legislation worldwide, has motivated to seek for recycling of wastes to get that wanted metals. In this way, the recovery of precious metals from wastes is an ideal opportunity to get raw materials having additional value, because the involved processes can recover metals without losing their quality, saving energy in comparison with the primary process of recovery, also reducing emissions, decreasing mining activities and the most important, reducing wastes that could be harmful to humankind and environment [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ilyas et al [4] summarized methods of bio-recovery from secondary resources for strategic and energy critical metals, such as rare earth elements, precious metals, and a common nuclear fuel element; they also suggested that sustainable recycling could be achieved by means of bio-metallurgy. Reyes-Valderrama et al [5] performed a voltammetry study for the recovery of Cu, Zn, and Ni from an e-waste leach solution to understand the behaviors of leaching and electrodeposition; they also reported selective electro-deposition with different pHs. Increasing attention has been paid to the leaching of refractory materials.…”
Section: Selective Extraction Of Valuable Metals From Wastsmentioning
confidence: 99%
“…Undoubtedly, leaching and electro-wining/electro-refining process have always been attached and both became part of the first basis to establish hydrometallurgy as a formal study (Dutta et al, 2018), (Reyes-Valderrama et al, 2017), (Yang et al, 2018), (Liu et al, (2017), (Kasper et al, 2016), (Memon et al, 2017), (Zhang et al, 2018), (Mooiman et al, 2005). In order to reinforce this relationship more, if it is possible the aim of this paper which is to obtain precious metals using an environmental friendly treatment of electronic waste.…”
Section: Introductionmentioning
confidence: 99%